LEGAL CONSEQUENCES OF MICRO AND SMALL ENTERPRISES ON HALAL CERTIFICATION OBLIGATIONS - Suriyadi; Muhammad Azhar Nur; Mutmainnah (El-Iqthisadi, 2025)
Abstract Islam provides guidance and guidance for humans in all aspects, one of which is the command to eat halal and good food. As a country that has a majority Muslim population, consumer protection in the form of guarantees of halal products is carried out. The Halal Product Guarantee Law has regulated the obligation to carry out halal certification, including micro and small business actors, so there is an obligation to carry out halal certification for their products. The research method used in this research is normative legal research using a statutory approach and a normative theological approach to study the obligation of halal certification based on the provisions of applicable laws and regulations and based on sources of Islamic law. The implementation of halal product guarantees has been regulated in such a way in statutory regulations that require all business actors to carry out halal certification, including micro and small business actors, by providing an easy halal certification process in the form of a statement (self-declare) with the provisions on the type of product and business actor that has been implemented. regulated in BPJPH regulations. Sanctions against micro and small business actors who do not carry out halal certification are not regulated so violations of this obligation are interpreted based on the provisions for violations of halal product guarantees which carry the threat of sanctions in the form of administrative sanctions, but the form of violation of halal product guarantees which is threatened with sanctions is not clearly stated. administratively, but if you look at the provisions of statutory regulations, sanctions can be in the form of written warnings, fines, and even withdrawal of goods from circulation. in the context of halal certification, micro, and small business actors need to implement regulations from Law 6 of 2023 regarding halal product guarantees Keywords: Halal Product, Self Declare, Micro and Small Enterprises